Synthesis of Nanoscale TiO2 and Study of the Effect of Their Crystal Structure on Single Cell Response - Z. R. Ismagilov; N. V. Shikina; N. A. Mazurkova; L. T. Tsikoza; F. V. Tuzikov; V. A. Ushakov; A. V. Ishchenko; N. A. Rudina; D. V. Korneev; E. I. Ryabchikova (The Scientific World Journal)
To study the effect of nanoscale titanium dioxide (TiO2) on cell responses, we synthesized four modifications of the TiO2 (amorphous, anatase, brookite, and rutile) capable of keeping their physicochemical characteristics in a cell culture medium. The modifications of nanoscale TiO2 were obtained by hydrolysis of TiCl4 and Ti(i-OC3H7)4 (TIP) upon variation of the synthesis conditions; their textural, morphological, structural, and dispersion characteristics were examined by a set of physicochemical methods: XRD, BET, SAXS, DLS, AFM, SEM, and HR-TEM. The effect of synthesis conditions (nature of precursor, pH, temperature, and addition of a complexing agent) on the structural-dispersion properties of TiO2 nanoparticles was studied. The hydrolysis methods providing the preparation of amorphous, anatase, brookite, and rutile modifications of TiO2 nanoparticles 3–5 nm in size were selected. Examination of different forms of TiO2 nanoparticles interaction with MDCK cells by transmission electron microscopy of ultrathin sections revealed different cell responses after treatment with different crystalline modifications and amorphous form of TiO2. The obtained results allowed us to conclude that direct contact of the nanoparticles with cell plasma membrane is the primary and critical step of their interaction and defines a subsequent response of the cell.